Intervensi Penguatan Membaca Kritis melalui Debat Literasi Berbasis Deep Learning dengan Teks Autentik-Digital pada Website Edukasi di SMA Kota Kediri - Andri Pitoyo; Sujarwoko Sujarwoko; Risa Helilintar; Sherly Nur Azizah; Siiti Chalimatus Sa'diyah (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study developed and tested an integrative learning model to improve the critical reading skills of high school students in Kediri City through a deep learning approach, authentic digital texts, and literacy debates based on educational websites. Using a quasi-experimental design with a pretest-posttest control group, it involved 240 eleventh-grade students from eight high schools in three subdistricts. The t-test confirmed a significant difference (p < 0.001). This model effectively improves the ability to analyze, evaluate, and synthesize information, supporting 21st-century literacy, the “Merdeka Belajar” (Freedom of Learning) vision, and SDG 4 on quality education. This research provides an empirical solution to the low level of critical literacy in Indonesia and has the potential to become a reference for education policies that are responsive to global challenges.